Strategies for Developing a Remote Destination: The Sharing Economy in Local Communities - DJUMRIANTI, Djumrianti; OSSEO-ASARE, Osseo-Asare (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505/jemt.12.1(49).13, 2021)
This study investigates the concept of sharing economy in the strategic development of a local community into a remote tourism destination, using a case study methodology. The overarching aim is to better understand how the application of the notion of sharing economy can help develop a locality as a remote destination.The locality in this study is ‘Pahawang’, South Lampung, Indonesia – a beautiful coral and marine tourism established by the local community. A mix of observationaland semi-structured interviews techniques were used to collect primary data relating to various themes e.g . strategies for using natural resources in Pahawang, traditional properties for enhancing the local economic, and the multiplier effects of tourism to the locals in Pahawang. Based on the empirical findings emanating from the thematic primary data analysis, we conclude by proposing a strategic sharing economy framework for the development of Pahawang as a remote tourism destination - it addresses six critical factors: cooperations among stakeholders; compactness of local women; support for the ‘ibu-ibu’ in public kitchens in providing meals; involvement of tourists in the local societies’ lives as a natural attraction; training local guides to make them more professional; and the strategic role of the Indonesian Government.